Contact sensitizations to disinfectants containing alcohols or quaternary ammonium compounds are rarely of clinical relevance. (4th April 2021) - Kreipe, Katharina; Forkel, Susann; Heinemann, Kim‐Elisabeth; Amschler, Katharina; Fuchs, Thomas; Geier, Johannes; Buhl, Timo
Abstract: Background: The use of disinfectants is part of the everyday life of people, especially in the medical profession. During the coronavirus disease 2019 (COVID‐19) pandemic, the use of disinfectants continues to increase and is of fundamental importance in infection control. Objectives: To determine the frequency of sensitization and the value of patch testing to didecyldimethylammonium chloride (DDAC) and the alcohols ethanol, 1‐propanol, and isopropanol. Methods: Clinical patch test data of 145 patients with suspected contact allergy to disinfectants were retrospective analysed. Results: Among the 145 patients patch tested with the different alcohols, only one nurse was detected with a possible allergy to 1‐propanol. Additional patch testing in 84 patients with DDAC 0.05% resulted in five patients with weakly positive reactions only, without clinical relevance. Patch testing with DDAC 0.03% showed no positive reactions at all on day 3 readings. Conclusions: DDAC and alcohols are rarely responsible for allergic contact dermatitis. The accused products of the patients should be checked for other allergens and further additives with skin‐irritating properties. Individual susceptibility and mishandling of the disinfectants should be considered.